A method for sensor placement taking into account diagnosability criteria - Yassine, Abed Alrahim; Ploix, Stéphane; Flaus, Jean-Marie (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a new approach to sensor placement based on diagnosability criteria. It is based on the study of structural matrices. Properties of structural matrices regarding detectability, discriminability and diagnosability are established in order to be used by sensor placement methods.
Keywords: fault diagnosis; diagnosability; sensor placement; structural modelling